The Regularity of Antenatal Care through Knowledge of Pregnant Women and Support from Husbands - Sendy Ayu Mitra Uktutias; Ade Ayu Mitra Ramadita Daluas; Sri Iswati; Cholichul Hadi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Pregnant women’s knowledge and husband’s support are factors that influence antenatal care regularity. Thisstudy aims to analyze the effect of knowledge of pregnant women and husband’s support on antenatal careregularity. This study a cross-sectional design and was conducted on 38 pregnant women as respondentsusing linear regression statistical tests. The result showed that there was an effect of knowledge of pregnantwomen and the husband’s support on the regularity of antenatal care. The better the knowledge of pregnantwomen about their pregnancy and the higher the support of their husbands will have an impact on theregularity of antenatal care. The implication of this research is for midwives who are at the forefront ofempowering cadres and providing health education to pregnant women and husbands about the importanceof regular antenatal care. Also, midwives need to improve competence through midwifery training efforts.